The effects of tourists on bird diversity in tourist area compared to restricted area of seasonal evergreen forest at Tung Salang Luang National Park, Phetchabun Province, Thailand - Nakwa A. (2014)
A survey of bird similarity, diversity and density were carried out at Tung Salang Luang National Park during March 2004 - February 2005, in 3 sites of seasonal evergreen forest, one site in a restricted area (SE1) and two sites in tourist areas (SE2 and SE3). Three sites were located in the same forest structure. The point count and line transect methods were used for data collection. The results revealed the following information: 133 species, 34 families and 11 orders of birds in SE1 (102 species), SE2 (100 species) and SE3 (89 species) were observed. Seven species of birds in all sites i.e. Criniger pallidus, Hypsipetes propinquus, Pycnonotus meianicterus, Irena puella, Garrulax leucolophus, Yuhina zantholeuca and Gracula religiosa were the co-dominant species in this forest that will be used indicator for future investigation. Base on similarity, tourist activities may be disturbed some bird groups in tourist area such as carnivorous and omnivorous (SE2 and SE3) and nectarivorous (SE3); base on densities, carnivorous (SE3), nectarivorous (SE2 and SE3) and garnivorous (SE3) were decreased 46-78 % in tourist sites compared with restricted site (SE1). Moreover, bird diversity index in restricted area was higher value than tourist area. This phenomenon indicated that some bird groups in tourist area at the seasonal evergreen forest had negative effect conelation with human activities and similarity, diversity and density indices were a proper indicator for further impact investigation for conservation and management strategies of avifauna. Finally, this result was the first report about avifauna dynamic of Tung Salang Luang National Park. © 2008 Academic Journals Inc.